2021
DOI: 10.1186/s12889-021-12187-5
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and e-health literacy among Arabic-speaking migrants in Sweden: a cross-sectional study

Abstract: Background Health inequities arise when the public cannot access and understand health information in an easy, accessible, and understandable way. Evidence supports that health literacy (HL) is a determinant for health outcomes, and when HL is limited this may have a major impact on morbidity as well as mortality. Migrants are known to have limited HL. Therefore, this study aimed to explore comprehensive health literacy (CHL) and electronic health literacy (eHL) among Arabic-speaking migrants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 56 publications
4
32
2
3
Order By: Relevance
“…Research studies on health literacy levels of ethnic minorities have been conducted in Turkey, Sweden, and China ( 8 , 22 , 23 ), and these studies share the understanding that low levels of health literacy are evident in ethnic minorities; however, further individual differences lack relevant research work. This study refined the understanding of the health literacy of residents in ethnic minority areas as reflected in the focus of their KAP scores through the common chronic disease KAP questionnaire and subsequent latent profile analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies on health literacy levels of ethnic minorities have been conducted in Turkey, Sweden, and China ( 8 , 22 , 23 ), and these studies share the understanding that low levels of health literacy are evident in ethnic minorities; however, further individual differences lack relevant research work. This study refined the understanding of the health literacy of residents in ethnic minority areas as reflected in the focus of their KAP scores through the common chronic disease KAP questionnaire and subsequent latent profile analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, health literacy is not easily quantifiable, especially considering that “it (health literacy) is a dynamic construct that emerges from the interaction between patients/citizens and health care systems, organizations, and professionals” ( 7 ). Generally speaking, ethnic minority populations are at a low level of health literacy, and it is our concern to improve their health literacy through effective intervention strategies ( 8 10 ). Thus, it is a priority to understand the nature of their health literacy.…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish context, research has shown that newly arrived migrants have limited health literacy and ask for more information on health-related issues, as well as that the healthcare services sometimes take it for granted that migrants have the same general health knowledge as people who have grown up in Sweden ( 7 ). In regard to health literacy, or the knowledge, motivation and, competencies to access, understand, appraise and apply information relevant to health ( 8 ), migrants have been reported to have limited levels of health literacy both in Europe ( 9 , 10 ) and Sweden ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the United States, Canada and Australia mostly shows large proportions of low health literacy among ethnic minorities or migrants, including Asians, Latin Americans, former Soviet Union migrants and other ethnic groups (10)(11)(12)(13)(14). In Europe, this includes, for instance, migrants with refugee status and Arabic-speaking migrants in Sweden (15,16), women from Somalia and different migration groups in Norway (17, 18), Russian-speaking migrants in Israel (19), Turkish, Portuguese and former Yugoslavian migrants in Switzerland and Austria (20,21). To the best of our knowledge, research on migrants in Germany is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…characteristics such as self-efficacy, which imply that migrants are also self-determined actors. Additionally, migrant-specific aspects, such as low proficiency in the receiving country's language and a shorter duration of stay have been identified as factors associated with low health literacy (12,15,16,18,21,32,(44)(45)(46). Research considering second generation migrants is scarce (21).…”
Section: Introductionmentioning
confidence: 99%